Combined deletion and DNA methylation result in silencing of FAM107A gene in laryngeal tumors - Kiwerska K; Szaumkessel M; Paczkowska J; Bodnar M; Byzia E; Kowal E; Kostrzewska-Poczekaj M; Janiszewska J; Bednarek K; Jarmuż-Szymczak M; Kalinowicz E; Wierzbicka M; et al. (NATURE PUBLISHING GROUP, 2025)
Larynx squamous cell carcinoma (LSCC) is characterized by complex genotypes, with numerous abnormalities in various genes. Despite the progress in diagnosis and treatment of this disease, 5-year survival rates remain unsatisfactory. Therefore, the extended studies are conducted, with the aim to find genes, potentially implicated in this cancer. In this study, we focus on the FAM107A (3p14.3) gene, since we found its significantly reduced expression in LSCC by microarray profiling (Affymetrix U133 Plus 2.0 array). By RT-PCR we have confirmed complete FAM107A downregulation in laryngeal cancer cell lines (15/15) and primary tumors (21/21) and this finding was further supported by FAM107A protein immunohistochemistry (15/15). We further demonstrate that a combined two hit mechanism including loss of 3p and hypermethylation of FAM107A promoter region (in 9/15 cell lines (p < 0.0001) and in 15/21 primary tumors (p < 0.0001)) prevails in the gene transcriptional loss. As a proof of principle, we show that Decitabine - a hypomethylating agent – restores FAM107A expression (5 to 6 fold increase) in the UT-SCC-29 cell line, characterized by high DNA methylation. Therefore, we report the recurrent inactivation of FAM107A in LSCC, what may suggest that the gene is a promising tumor suppressor candidate involved in LSCC development.